Improvement of Speaking Skills Through the Use of Arabic as an Introduction Language (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many Arabic learning strategies have been used to improve speaking skills. However, it turns out that not everylearning strategy has succeeded in increasing speaking skills. This paper aims to understand (1) the contribution of usingArabic as the language of instruction, (2) the process of increasing student's speaking skills after attending lectures usingArabic as an introduction, and (3) analyzing efforts to improve the quality of lectures. So far, this aspect has not been paidattention to in existing studies. This research approach is qualitative with a case study model. The research data is collectedthrough interviews, observation, and documentation methods. Data analysis starts from data collection, data description, anddata reduction, then verification in detail. The results showed that students benefited from using Arabic as the language ofinstruction, namely the addition of new vocabulary and terms, mastery of sentence structures, and the courage to expressthemselves in Arabic. Improving speaking skills is characterized by increased self-confidence, fluency in speaking, and moreinformation to support speaking skills. The need to improve the quality of lectures by squeezing and the leader motivates thelecturers to use Arabic as the language of instruction, provides many opportunities for students to be active, and Arabicizationof linguistic terms is needed. The conclusion is that Arabic as an introduction to lectures can improve students' speaking skills.This article provides suggestions on the effective use of Arabic as a strategy for learning speaking skills.